2000
DOI: 10.1021/jp001881z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Vibrational Coherence in the Core Light-Harvesting Antenna of Rhodopseudomonas viridis

Abstract: In this paper we explain the wavelength-dependent oscillatory features in the pump−probe kinetics of the core LH1 antenna of Rhodopseudomonas viridis (Monshouwer, R.; Baltuška, A.; van Mourik, F.; van Grondelle, R. J. Phys. Chem. A 1998, 102, 4360). A quantitative fit of the data was obtained using the doorway−window representation of the nonlinear optical response in the vibrational eigenstate basis. In contrast to LH1/LH2 complexes from the BChl a-containing species, the LH1 antenna of Rps. viridis is chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 80 publications
2
45
0
Order By: Relevance
“…Recent interest in quantum-coherent dynamics has been based on the expectation that the cross-peak oscillations were signatures of electronic coherences and not signatures of vibrational coherences (intramolecular nuclear wavepackets oscillating on either the excited or ground electronic potentials). Numerous recent studies [35][36][37][38][39][40][41][42]69 have pointed out that using 2D ES to distinguish between vibrational and electronic coherences can be challenging because their spectral signatures are very similar.…”
Section: Assignment Of Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent interest in quantum-coherent dynamics has been based on the expectation that the cross-peak oscillations were signatures of electronic coherences and not signatures of vibrational coherences (intramolecular nuclear wavepackets oscillating on either the excited or ground electronic potentials). Numerous recent studies [35][36][37][38][39][40][41][42]69 have pointed out that using 2D ES to distinguish between vibrational and electronic coherences can be challenging because their spectral signatures are very similar.…”
Section: Assignment Of Oscillationsmentioning
confidence: 99%
“…24,25 Given that 2D ES was only recently developed, 26,27 many research groups 10,11,[28][29][30][31][32][33][34] continue to develop experimental apparatus suitable for recording high-quality spectra. Studies have also pointed out the similarities [35][36][37][38][39][40][41][42] and differences 10 between the signatures of vibrational and electronic coherences in 2D ES. Below we isolate several contributions to the coherent dynamics by creation and manipulation of the 3D spectral solid (3D ES), which allows us to investigate the dynamics in detail.…”
Section: Introductionmentioning
confidence: 99%
“…A recent theoretical study viewing EET in molecular dimers as an electronic potential energy surface-crossing process, 30, see also 31 showed that the vibrational coherence transfer that naturally accompanies electronic excitation transfer can give rise to quantum beats in time-resolved polarized emission spectra that are in-phase between parallel and perpendicular emission channels, as had been observed in the LH-1 antenna of photosynthetic bacteria. 24,32,33 Those calculations on a model complex composed of two identical chromophores, each supporting a single harmonic vibrational mode, demonstrated that vibrational coherence transfer is a consequence of the nuclear motion resulting from short-pulse excitation to the Franck-Condon point of a site-excited state (the donor-excited state). The periodic return of this localized wave packet to the surfacecrossing seam (q a = q b ), where amplitude can be transferred to the acceptor-excited state, results in a stepwise decrease in donor population (see Fig.…”
Section: A Control Schemementioning
confidence: 99%
“…The dynamic disorder leads to a broadening of the exciton levels E(k) with a FWHM = 58 cm −1 = J/6.5. Novoderezhkin et al [19,20] fitted the pump-probe spectra of the LH2 antenna. Taking into account the difference between the local BChl energies ∆ǫ = ǫ 1 − ǫ 2 in the basic dimer which leads to the splitting of the exciton energy band to two subbands, the following set of microscopic parameters : the transfer integrals J 12 = 400 cm −1 , J 23 = 290 cm −1 , the the homogeneous line widths of exciton states in the lower subband Γ 1L = 240 cm −1 and in the higher subband Γ 1H = 340 cm −1 and the strength of the static disorder ∆ = 450 cm −1 has been used.…”
Section: Microscopic Parametersmentioning
confidence: 99%
“…Multitime correlation functions entering the equations of motion can be calculated from two-time correlation functions (20) according to different rules. Mostly dichotomic, Gaussian and white noise statistics have been applied in the past.…”
Section: Stochastic Theoriesmentioning
confidence: 99%